Perancangan dan Penerapan Jalur Evakuasi Darurat Berbasis Prinsip Kesehatan dan Keselamatan Kerja (K3) di SD Negeri 074 Ayudia Kota Bandung - Anzelin Dwi Alma Julianty; Dewi Rahmawati; R. Cahyadi Nugraha (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study addresses the critical need for structured disaster mitigation frameworks in primary education facilities by designing and implementing an ergonomics based emergency evacuation system at SD Negeri 074 Ayudia, Bandung. Integrating Occupational Health and Safety principles, the research optimizes visual signage dimensions and spatial layout through meticulous calculations of anthropometric properties of Indonesian primary students. Mathematical formulas for stroke width and letter height were executed to eliminate visual blind spots, while architectural circulation pathways were strategically mapped toward two distinct safe assembly zones to prevent dangerous bottlenecks. Post intervention empirical validation demonstrated a significant increase in emergency circulation literacy and signage legibility. The findings underscore that combining standardized physical safety infrastructure with periodic simulations successfully transforms passive hazard awareness into a resilient, long term safety culture within urban school environments.